2002
DOI: 10.1074/jbc.m205085200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucocorticoid-induced Apoptosis in 697 Pre-B Lymphocytes by the Mineralocorticoid Receptor N-terminal Domain

Abstract: The glucocorticoid and mineralocorticoid receptors (GR and MR) share considerable structural and functional homology and bind as homodimers to hormoneresponse elements. We have shown previously that MR and GR can form heterodimers that inhibit transcription from a glucocorticoid (GC)-responsive gene and that this inhibition was mediated by the N-terminal domain (NTD) of MR. In this report, we examined the effect of NTD-MR on GC-induced apoptosis in the GC-sensitive pre-B lymphoma cell line, 697. In GC-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 66 publications
8
28
2
Order By: Relevance
“…This MR-mediated repression of GR activity has also been described in mammals and seems to be a typical outcome of GR and MR co-localization (Liu et al 1995, Derfoul et al 1998, Ou et al 2001, Planey et al 2002, although synergistic transcriptional activation between the GR and the MR was also described by Trapp et al (1994). Such observations of mutual inhibition of transcriptional activity have also been described with androgen and GRs, which is consistent with a high degree of sequence homology in the dimer interface of DBD between these nuclear receptors (Chen et al 1997).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This MR-mediated repression of GR activity has also been described in mammals and seems to be a typical outcome of GR and MR co-localization (Liu et al 1995, Derfoul et al 1998, Ou et al 2001, Planey et al 2002, although synergistic transcriptional activation between the GR and the MR was also described by Trapp et al (1994). Such observations of mutual inhibition of transcriptional activity have also been described with androgen and GRs, which is consistent with a high degree of sequence homology in the dimer interface of DBD between these nuclear receptors (Chen et al 1997).…”
Section: Discussionsupporting
confidence: 69%
“…Thus, study of the regulation of the human Na/K-ATPase beta1 subunit promoter in CV1 cells has shown that MR interaction with the GR on the promoter effectively down-regulates transcription, and this inhibition was mediated by the N-terminal domain of the MR (NTD-MR) (Derfoul et al 1998). More recently, the effect of the NTD-MR on glucocorticoid-induced apoptosis in the glucocorticoid-sensitive pre-B lymphoma cell line was analyzed, and results suggest that the NTD-MR mediates the inhibition of glucocorticoid-regulated gene transcription by glucocorticoids (GC) through heterodimerization with the GR (Planey et al 2002). In neuronal cells, there is also evidence that heterodimerization of the MR and the GR mediates direct corticosteroid-induced trans-repression of the 5-HT1A receptor promoter (Ou et al 2001).…”
Section: Figurementioning
confidence: 99%
“…19,31 However, a similar mechanism does not appear to operate in the case of autocrine regulation mediated by active GCs since total GR expression was constant throughout differentiation ( Figure 1C; our unpublished data). Furthermore, we have detected no evidence of increased expression of either GR␤ or the mineralocorticoid receptor (both of which may act as receptor "decoys" 22,42 ) in mature DCs. These findings suggest that other GR-independent factors such as postreceptor accessory pathways (eg, invoked by nuclear factor-B activation) contribute to GC resistance.…”
Section: Discussionmentioning
confidence: 85%
“…Glucocorticoid treatment caused repression of BCL2A1 mRNA expression in lymphoma and thymocyte cell lines [25,26]. In addition, direct fetal cortisol infusion and maternal betamethasone administration in sheep have been shown to reduce the number of binucleate cells [15,16].…”
Section: Discussionmentioning
confidence: 99%